Prevalence of depression in type-2 diabetes mellitus patients of Khyber Pakhtunkhwa - Ahmad, Aleena; Khan, Khansa; Ullah, Syed Mazhar; Zareef, Adil; Ali, Waqar (International Journal of Pathology, 2025)
Background: Diabetes Mellitus (DM) is a chronic metabolic condition and carries an increased risk of development of disease complications. The diagnoses of it raises the likelihood of incident depression. This study was aimed to determine the prevalence of depression among type-2 diabetes mellitus patients and the factors associated with it. Methods: This was a cross-sectional study carried out at endocrinology outpatient department of Northwest General Hospital and Northwest teaching hospital from December 2022 to June 2023. Patients with diagnosis of type-2 diabetes ≥1 year participated in this study. Pregnant and postpartum women were excluded from the study. PHQ-9 scale was used to assess the level of depression of the participants. All the data was analyzed using SPSS version 26.0. Results: Out of 256 patients that participated in the study, 49.2% were males and 50.8% were females. 80.5% of the patients had some level of depression. 26.6% had mild depression, 31.3% had moderate depression, 15.6% had moderately severe depression and 7% patients suffered from severe depression. There was a statistically significant difference between the mean depression score of the various age groups (p<0.05), males and females (p<0.05), participants who had diabetes for less than 10 years and those that had diabetes for more than 10 years (p<0.05), patients who had developed diabetic complications and those that did not have any complications (p<0.05). Conclusion: Some level of depression was found among majority of the patients. Patients of older age groups, females, longer duration of diabetes and those who had developed diabetic complications were found to have higher level of depression.